2009
DOI: 10.1039/b912820d
|View full text |Cite
|
Sign up to set email alerts
|

A molecular dynamics simulation study of LiFePO4/electrolyte interfaces: structure and Li+ transport in carbonate and ionic liquid electrolytes

Abstract: We have performed atomistic molecular dynamics (MD) simulations of the (010) surface of LiFePO(4) in contact with an organic liquid electrolyte (OLE), ethylene carbonate : dimethyl carbonate (3 : 7) with approximately 1 mol kg(-1) LiPF(6), and an ionic liquid-based electrolyte (ILE), 1-ethyl 3-methyl-imidazolium: bis(fluorosulfonyl)imide (EMIM(+) : FSI(-)) with approximately 1 mol kg(-1) LiFSI. Surface-induced structure that extends about 1 nm from the LiFePO(4) surface was observed in both electrolytes. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 36 publications
3
67
1
1
Order By: Relevance
“…In polarizable simulations of pyr 13 TFSI, pyr 14 TFSI, pyr 14 TFSI, and emimFSI doped with LiTFSI or LiFSI salts [53,[85][86][87][88], the Li + cation was found to be coordinated, on average, by roughly four oxygen atoms. Both monodentate (one oxygen of TFSI bound to a Li + ) and bidendate (two oxygens of TFSI bound to a Li + ) coordinations were observed with a preference for the monodentate configuration in contrast to the conclusions of infrared and Raman studies of alkyl-substituted imidazolium-TFSIbased IL doped with LiTFSI [94].…”
Section: Modeling Of Ionic Liquid Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…In polarizable simulations of pyr 13 TFSI, pyr 14 TFSI, pyr 14 TFSI, and emimFSI doped with LiTFSI or LiFSI salts [53,[85][86][87][88], the Li + cation was found to be coordinated, on average, by roughly four oxygen atoms. Both monodentate (one oxygen of TFSI bound to a Li + ) and bidendate (two oxygens of TFSI bound to a Li + ) coordinations were observed with a preference for the monodentate configuration in contrast to the conclusions of infrared and Raman studies of alkyl-substituted imidazolium-TFSIbased IL doped with LiTFSI [94].…”
Section: Modeling Of Ionic Liquid Electrolytesmentioning
confidence: 99%
“…[53,[85][86][87][88] and nonpolarizable [89,90] force fields were used in these simulations. MD simulations employing polarizable force fields predicted Li + transport in pyr 14 TFSI doped with LiTFSI below experimental values [86], while MD using nonpolarizable force fields predicted significantly slower ion transport.…”
Section: Modeling Of Ionic Liquid Electrolytesmentioning
confidence: 99%
“…Due to strong polarization of anions by a small Li + cation, it is important to include many-body polarizable terms in the intermolecular potential (force field) used in MD simulations. Previous simulations using atomic polarizable force field for liquids, electrolytes and polymer (APPLE&P) have accurately predicted both structural and transport properties of pure ILs and IL doped with Li + salts [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent papers, however, indicate that battery electrolytes with LiFSI have very promising properties-i.e., a relatively high thermal and hydrolytic stability (relative to LiPF 6 ), a high conductivity (comparable to electrolytes with LiPF 6 ) and a wide liquidus range. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] One key concern originated from reports which indicated that the use of the LiFSI salt in electrolytes results in severe corrosion of the battery Al current collector at high potentials. 3,15 It has recently been demonstrated, however, that this was likely due to chloride impurities in the salt (from the synthesis procedures) rather than the LiFSI salt itself.…”
mentioning
confidence: 99%